2006
DOI: 10.1889/1.2433466
|View full text |Cite
|
Sign up to set email alerts
|

P-16: Integration of the 4.5ʺ Active Matrix Organic Light-emitting Display with Organic Transistors

Abstract: We developed an active matrix organic light‐emitting display(OLED) on a glass using two organic thin‐film transistors(OTFTs) and a capacitor in a pixel. The OTFTs has bottom contact structure with a unique gate insulator and pentacene for the active layer. The width and length of the switching OTFT is 500 μm and 10 μm respectively and the driving OTFT has 900 μm channel width with the same channel length. The characteristics of the OTFTs were examined by test cells around display area and generated images on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Zhou et al reported a 48 × 48 pixels OTFT‐OLED in which a pentacene layer was patterned by photolithography on a plastic substrate [poly(ehtylene terephthalate), PET] 35. Choi et al demonstrated 12 × 12 pixels OTFT‐OLED on a glass,36 Han et al demonstrated a 124 × 94 pixels OTFT‐OLED on a plastic substrate (polyethersulfone, PES),37 and Lee et al demonstrated a 192 × 64 pixel OTFT‐OLED on a glass 38. Recently Suzuki et al reported a full‐color 213 × RGB × 120 pixels OTFT‐OLED panel on a plastic substrate (polyethylene naphthalate, PEN) 39…”
Section: Otft‐driven Flexible Oled Displaysmentioning
confidence: 99%
“…Zhou et al reported a 48 × 48 pixels OTFT‐OLED in which a pentacene layer was patterned by photolithography on a plastic substrate [poly(ehtylene terephthalate), PET] 35. Choi et al demonstrated 12 × 12 pixels OTFT‐OLED on a glass,36 Han et al demonstrated a 124 × 94 pixels OTFT‐OLED on a plastic substrate (polyethersulfone, PES),37 and Lee et al demonstrated a 192 × 64 pixel OTFT‐OLED on a glass 38. Recently Suzuki et al reported a full‐color 213 × RGB × 120 pixels OTFT‐OLED panel on a plastic substrate (polyethylene naphthalate, PEN) 39…”
Section: Otft‐driven Flexible Oled Displaysmentioning
confidence: 99%
“…Because of the above areal uniformity issue, most of the backplane OTFT arrays for display applications available in the literature are reported to be fabricated by either vacuum deposition of small molecules or spin‐coating followed by lithographic patterning of the spin‐cast films. The latter methods are more favorable than inkjet printing in terms of areal uniformity of OTFT performance …”
mentioning
confidence: 99%